The ultimate guide to weight training for volleyball - Price, Robert G., ....- (2005)
The Ultimate Guide to Weight Training for Volleyball is the most comprehensive and up-to-date volleyball-specific training guide in the world today. It contains descriptions and photographs of nearly 100 of the most effective weight training, flexibility, and abdominal exercises used by athletes worldwide. This book features year-round volleyball-specific weight-training programs guaranteed to improve your performance and get you results. No other volleyball book to date has been so well designed, so easy to use, and so committed to weight training. This book will have you serving with a higher velocity and overall effectiveness. Volleyball players of all skill levels will be able to leap higher, shift quicker, and flat-out play better due to an increase in overall strength and agility. Your spikes, kills, and blocks will all become shaper and more effective and your stamina and endurance will allow you to keep the intensity up until the final point in every match. Both beginners and advanced athletes and weight trainers can follow this book and utilize its programs. From recreational to professional, thousands of athletes all over the world are already benefiting from this book and its techniques, and now you can too!
Maximize your athletic potential on the volleyball court! - Pre-season, in-season, and off-season sport-specific programs designed to: increase speed, eliminate fatigue and prevent injuries
Keywords: Volleybal ; krachttraining